Salinity-alkalinity gradients and biocrust types jointly shape bacterial community assembly and carbon‑nitrogen functioning in dryland soils surrounding playas in northeast Spain - Shubin Lan; Andrew D. Thomas; Stephen Tooth; Ian Saunders (CATENA, 2026)

Are human activities or climate changes the main causes of soil erosion in the South African drylands?: A palaeo‐perspective from three sites in the interior - Richard Lyons; Stephen Tooth; Geoff A. T. Duller; Terence McCarthy (Journal of Quaternary Science, 2024)
Soil erosion across South Africa's drylands occurs widely in the form of gullies and badlands (locally termed dongas) that have developed in colluvium and in valley fills along incised rivers. This erosion has commonly been attributed to land mismanagement, particularly since European settlement, but natural factors such as soil properties, local base level fall and climate change have also been invoked. To disentangle human and natural factors, we use optically stimulated luminescence (OSL) dating, supported by documentary and archaeological evidence, to constrain the timing and causes of donga formation at three widely spaced sites across interior South Africa. At all three sites, the exposed stratigraphy indicates that hillslopes and floodplains underwent net sediment accumulation during most of the late Quaternary, and that present‐day deep erosion is of a magnitude unprecedented probably within at least the past 100 ka. OSL ages indicate that the onset of erosion at each site significantly pre‐dates European incursion and instead was broadly coincident with abrupt climatic changes that occurred during the Medieval Climatic Anomaly (MCA, ~ ad 900–1300) and Little Ice Age (LIA, ~ ad 1300–1800). Based on correlation with palaeoclimate proxy records, we propose that erosion was triggered by abrupt hydroclimatic oscillations during the MCA, and continued during the LIA in response to climate‐driven, large floods. At these sites, soil type and local base level falls exert secondary controls on the specific locations, processes, rates and depths of erosion. In other areas of South Africa, clear links between land mismanagement and soil erosion have been demonstrated, but for sites where detailed investigations have yet to be undertaken, these findings challenge an often default assumption that soil erosion is necessarily attributable to human factors. Our findings have significant implications for soil erosion control strategies and assessment of South African dryland landscape response to future climate changes.

Interactions between vegetation and river morphodynamics. Part I: Research clarifications and challenges - Dov Corenblit; Hervé Piégay; Florent Arrignon; Eduardo González-Sargas; Anne Bonis; Neil S. Davies; Dav M. Ebengo; Virginia Garófano-Gómez; Angela M. Gurnell; Annie L. Henry; Borbála Hortobágyi; Francisco Martínez-Capel; et al. (Earth-Science Reviews, 2024)

Interactions between vegetation and river morphodynamics. Part II: Why is a functional trait framework important? - Dov Corenblit; Hervé Piégay; Florent Arrignon; Eduardo González-Sargas; Anne Bonis; Dav M. Ebengo; Virginia Garófano-Gómez; Angela M. Gurnell; Annie L. Henry; Borbála Hortobágyi; Francisco Martínez-Capel; Lucas Mazal; et al. (Earth-Science Reviews, 2024)

Book Review - Stephen Tooth (Proceedings of the Geologists' Association, 2023)

Crevasse splay morphodynamics near a non-vegetated, ephemeral river terminus: Insights from process-based modelling - Jiaguang Li; Helena van der Vegt; Joep E.A. Storms; Stephen Tooth (Journal of Hydrology, 2023)

Wetlands in drylands: diverse perspectives for dynamic landscapes - Suzanne Grenfell; Michael Grenfell; Stephen Tooth; Adriana Mehl; Emily O’Gorman; Tim Ralph; William Ellery (Wetlands Ecology and Management, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)